Description Of Perineum Rupture Events On Mothers In Public Health Tanete - Risnawati; Andi Tenri Fajriani (Lembaga Penelitian dan Pengabdian Masyarakat, Stikes Panrita Husada Bulukumba, 2018)
Perineal rupture is a wound in the perineum that often occurs during labor, this is due to sudden pressure from the head or fetus so that the skin and tissue of the perineum tear. The purpose of this study was to determine the description of the incidence of rupture of the perineum in women in the Tanete health center. This type of research is descriptive which only describes or describes. The population is all maternal women who experienced perineum rupture at the Tanete Puskesmas in 2016 as many as 195 people. The sampling technique is total sampling with a total sample of 195 people. The instrument used was an observation sheet using secondary data. The results of the study were obtained from 195 recorded cases, the most age-related characteristics were 20-35 years (75.4%), most maternal education with a secondary education level of 110 (56.4%), maternal parity was mostly Primipara namely 120 (61.5%), while the highest birth weight was> 3000 grams, namely 103 (52.8%). The conclusion in this study is the incidence of perineal rupture is dominated by mothers aged 20-35 years of secondary education, Primipara, and BBL> 3000 grams. It is recommended for further researchers to examine the relationship between some characteristics that exist in the mother.